2002
DOI: 10.1001/archinte.162.8.901
|View full text |Cite
|
Sign up to set email alerts
|

Anger in Young Men and Subsequent Premature Cardiovascular Disease

Abstract: High level of anger in response to stress in young men is associated with an increased risk of subsequent premature CVD, particularly myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 34 publications
3
69
1
3
Order By: Relevance
“…exercise and smoking). These findings were in line with those studies that have shown that individuals who experience negative emotions, such as depression, were at an increased risk of CAD (12,25,26). In a cohort of 7,709 patients with confirmed CAD but without a diagnosis of heart failure or depression, a subsequent diagnosis of depression was associated with 50% increase in the risk of heart failure (14).…”
Section: Discussionsupporting
confidence: 91%
“…exercise and smoking). These findings were in line with those studies that have shown that individuals who experience negative emotions, such as depression, were at an increased risk of CAD (12,25,26). In a cohort of 7,709 patients with confirmed CAD but without a diagnosis of heart failure or depression, a subsequent diagnosis of depression was associated with 50% increase in the risk of heart failure (14).…”
Section: Discussionsupporting
confidence: 91%
“…This raises the possibility that individuals high in aggressiveness are at increased risk of inflammatory disease. In this regard, consistent prospective evidence shows that dispositional anger/hostility predicts incidence and progression of cardiovascular disease (e.g., Chang et al, 2002;Everson et al, 1998;Kawachi et al, 1996;Koskenvuo et al 1988), which is widely accepted to be of inflammatory etiology (Ridker et al, 2000a(Ridker et al, , 2000bRoss, 1999). Further research is warranted to determine if it is the behavioral component of these antagonistic dispositions that confers increased susceptibility to disease.…”
Section: Predictormentioning
confidence: 98%
“…Miller et al, 1996). Subsequent studies have indicated that selfreports of trait hostility and anger predict new coronary events among previously healthy people (Chang, Ford, Meoni, Wang, & Klag, 2002;Everson et al, 1997;Kawachi, Sparrow, Spiro, Vokonas, & Weiss, 1996; J. E. . Further, selfreports of hostility have been associated with the severity and progression of atherosclerosis (Iribarren et al, 2000;Julkunen, Salonen, Kaplan, Chesney, & Salonen, 1994;Matthews, Owens, Kuller, Sutton-Tyrrell, & Jansen-McWilliams, 1998;Whiteman, Dreary, & Fowkes, 2000), although there have been negative findings (O'Malley, Jones, Feuerstein, & Taylor, 2000).…”
Section: Hostility As the Toxic Component Of The Type A Patternmentioning
confidence: 99%